Strategi Pengembangan Objek Wisata Tepian Batang Mandau di Desa Balai Pungut Kecamatan Pinggir Kabupaten Bengkalis - Nelsa Putri; Hafzana Bedasari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Balai Pungut village has a lot of tourism potentials that could be develop to attract visitors more. A SWOT analysis that used in this study to evaluate how well strategies for developing tourism are working. The main goal of this research is to create a development strategy for the Tepian Batang Mandau destination site, while identifying the supporting and also inhibiting factors in that strategy. This research uses a qualitative approach and was carried out in Desa Balai Pungut, Pinggir District, Bengkalis Regency. The data collection was done through interviews, observation, and documentation. The data was then analyzed using SWOT analysis. The result shows that development strategies for Tepian Batang Mandau has been going well. Efforts have been made to improve its appeal, developed the better access, add some supporting facilities, and collaborate with the government to attract visitors more. From the SWOT analysis, absolutely that Tepian Batang Mandau has strong natural resources, which is a big advantage. However, there are still several weaknesses, especially in terms of supporting infrastructure. Some of the issues include a lack of clean water, limited lighting at the site, no directional signs to guide visitors, lack of cleanliness, and the unavailability of entrance tickets. These problems could make it harder for the site to grow and attract more tourists. On the bright side, the development of the site is supported by its tourism potential, its natural appeal, and the active involvement of local communities. Which said, there are also a lot of obstacles, such as poor infrastructure, low investment, lack of environmental awareness, limited skilled human resources, overlapping regulations, weak promotion, and lack of collaboration with investors. This study recommends that the community and local government should be cooperate to preserve the beauty of the site and take a good care of the existing facilities. This cooperation could be a main strategy in helping the Tepian Batang Mandau tourist destination grow and thrive.